Midlife Cardiovascular Risk Impacts Executive Function: Framingham Offspring Study - Nishtala, Arvind (2014)
INTRODUCTION: Novel error scores and traditional indices of executive function (EF) were related to cardiovascular risk factors (CVRF) measured 10–15 years earlier. METHODS: From 1991–1995, the Framingham Stroke Risk Profile (FSRP), a composite score of cardiovascular risk, was ascertained in 1755 Framingham Offspring participants (54% women, mean age= 54 ± 9 years). Participants were administered EF tests: FAS and Animals Fluency tests, Trail Making Test B (TrB), and Digit Span-Backwards (DS-B) in 2005–2009. Linear and logistic regression were used to relate the FSRP and its components to both error responses and traditional scores. RESULTS: Consistent with previous findings, the FSRP and the individual components diabetes and sex were associated with several traditional measures of EF. Of interest were relationships between the FSRP score and TrB Total Errors (p=0.04), DS-B % Total Errors (p=0.02) and DS-B Capacity Score (p=0.03), and prevalent CVD related to making FAS Perseverations in the 75th percentile (p=0.03). By comparison, FSRP and CVD were not related to the traditional DS-B or FAS scores. Additionally, age was associated with higher Animals % Total Errors and % Perseverations among ApoE4+ individuals and with higher TrB Total Errors among ApoE4− individuals. CONCLUSION: For those middle-aged and healthy, including those ApoE4+, CVRF are related to impairments in EF as ascertained by novel errors as well as traditional measures.